Determinants of Company Value Determinants of Company Value - Inda Tri Rahayu; Kamilatus Sa’diyah; Dodi Irawan (Sharia Economic and Management Business Journal (SEMBJ), 2024)
This research is qualitative research using a systematic literature review method. The data source in this research is secondary data in the form of journals that are relevant to the research theme. This research aims to determine the factors that can influence company value. The results of this research illustrate that profitability, leverage, company size, liquidity have an effect on company value, while company growth has no effect on company value.